Using fetal scalp stimulation with Doppler ultrasonography to enhance intermittent auscultation in low-resource settings: a diagnostic trial from Tanzania - David M. Goodman; Pendo Mlay; Nathan Thielman; Maria J. Small; John W. Schmitt (BMC, 2019)
Abstract Background Hypoxia during labor contributes to 2.2 million intrapartum and early neonatal deaths each year. An additional 0.6-1.0 million cases of life-long disability occur because of fetal hypoxia during labor. It is known that fetal heart rate changes in labor correspond to hypoxia and neurologic compromise, but a reliable, low-cost method for detecting these changes is not available. In this study we sought to compare the ability of a handheld Doppler device to detect accelerations as part of the fetal scalp stimulation test and to compare the diagnostic performance of routine intermittent auscultation with auscultation that is augmented with fetal scalp stimulation. Methods This non-randomized, pre- and post-diagnostic trial was conducted with 568 maternal-fetus pairs at Kilimanjaro Christian Medical Center in Moshi, Tanzania. The first objective was to determine whether a handheld Doppler device could detect fetal accelerations in labor with reasonable accuracy as compared with a cardiotocography machine. We performed the fetal scalp stimulation test on 50 fetuses during labor using both a handheld Doppler and a cardiotocography machine and compared the outcomes for correlation using the kappa correlation coefficient. During the second objective, two groups of laboring women were monitored either with intermittent auscultation alone per routine protocol (N = 251) or with intermittent auscultation augmented with fetal scalp stimulation per study protocol(N = 267). Diagnostic accuracy of the monitoring method was determined by comparing umbilical cord blood gases immediately after birth with the predicted state of the baby based on monitoring. The analyses included sensitivity, specificity, and positive and negative predictive values. Results The prevalence of fetal acidemia ranged from 15 to 20%. Adding the fetal scalp stimulation test to intermittent auscultation protocols improved the performance of intermittent auscultation for detecting severe acidemia (pH < 7.0) from 27 to 70% (p = 0.032). The negative predictive value of intermittent auscultation augmented with the fetal scalp stimulation test ranged from 88 to 99% for mild (pH < 7.2) to severe fetal acidemia. Conclusions The fetal scalp stimulation test, conducted with a handheld Doppler, is feasible and accurate in a limited resource setting. It is a low-cost solution that merits further evaluation to reduce intrapartum stillbirth and neonatal death in low-income countries. Trial registration ClinicalTrials.gov (NCT02862925).